Implementation of School Literacy Movement in Lower Grades (Study at SD Negeri 3 Pekuncen) - Urjuwan Afkar, Izdihar; Amirul Mukminin (Universitas Negeri Semarang, 2024)
This research is a case study research using a descriptive qualitative approach. The purpose of this research is to describe the implementation of literacy movement in lower grades at SD Negeri 3 Pekuncen. In addition, this study also aims to determine the supporting factors and inhibiting factors in the implementation of school literacy movement at SD Negeri 3 Pekuncen. Data collection techniques used are observation, interviews and documentation. Data analysis techniques use the version of Miles and Huberman (1994), namely data reduction, data presentation, and drawing conclusions. The primary data sources obtained by researchers from field observations and direct interviews with the principal and teachers of grades 1 to 4 of SD Negeri 3 Pekuncen. While the secondary data obtained by researchers are supporting documents in the form of RPP or learning implementation plans.The results of the study showed that the implementation of the literacy movement of reading and writing in the lower grades at SD Negeri 3 Pekuncen was carried out through habituation activities. This habituation activity was carried out 15 minutes before starting teaching and learning activities in the form of reading books for 15 minutes. However, in the research conducted by the researcher, there were several errors in the implementation of the literacy movement that had been running previously, this can be seen from the lower grades who could not read but were required to read 15 minutes before the implementation of teaching and learning activities. These are several factors that influence the implementation of the school literacy movement at SD Negeri 3 Pekuncen. These factors are supporting factors and inhibiting factors.